Branding Tourism's Image - Octafian, Ray; Mistriani, Nina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The tourism development strategy through the digital economy in building a brand image is very important in developing the tourism industry business. The role of Marketing Public Relations through brand image is the spearhead in maintaining the minds of consumers to be loyal and different from increasingly high competitors. The reason the researchers took this theme is the importance of the uniqueness of packaged tourism to shape economic activity through the use of information and communication technology that can affect the economy. This research was conducted at Curug Gondoriyo Semarang. The waterfall is one of the new tourist attractions in Semarang and is starting to be known to the public as a neglected natural tourism, but has a unique beautiful waterfall area with a height of 15 meters and is more attractive after being laid out. then promoted. Sources of research data are primary and secondary data. This study uses a qualitative research method. Methods of data collection through direct observation to the field, interviews, questionnaires. The results of the research are marketing public relations through social media with brand image opinion leaders, carrying out word of mouth techniques, conducting events as a media promotion and an ecotourism concept approach that preserves natural resources as the main issue in human life, both economically and socially.